Commodity Prices and the Stock Market in Thailand - Aumeboonsuke, Vesarach (International Journal of Energy Economics and Policy, 2020)
This study aims to investigate the association between Thai stock market and the commodity markets using twenty-year historical monthly data from January 2000 to January 2020. Commodity prices used in the research consist of the prices of crude oil, natural gas, liquified natural gas, commodity agricultural raw materials, and gold. The traditional VAR is used in analyzing the relations between the commodity prices and stock index. The findings show how changes in each commodity prices had significant influence on the stock market. Both evidences of a long-run and a short-run impacts are examined to determine if the past values of changes in the prices of energy, agricultural raw materials, and gold are important in predicting the developments in the stock market or not. The results from the study provide the evidence that Thai stock market is responsive to energy-related, precious metal, and commodity-related indicators. Keywords: Energy price Commodity price, Gold price, Stock return, Granger Causality, Vector Autoregressive JEL Classifications: E44, G10, Q43 DOI: https://doi.org/10.32479/ijeep.10298